Geology and Geological Structure of Potash and Rock Salt Deposits in Chalerm Phrakiat District, Nakhon Ratchasima Province in Northeastern Thailand - Parkorn Suwanich (Agriculture and Natural Resources, 2010)
Potash and rock salt minerals were examined from core holes drilled by the Department of Mineral Resources, Thailand in Chalerm Phrakiat district, Nakhon Ratchasima province in Northeast Thailand. In total, 7 boreholes were studied to explain the geology and geological structure of the potash and rock salt deposits. There were two beds of rock salt that made up the Middle and Lower Rock Salt units. However, some holes were found only in the Lower Salt bed. The potash minerals found only in the Lower Salt bed were both low grade “carnallite” and high grade “sylvite”, (one of the major Kelements used to produce chemical fertilizer), as well as the magnesium mineral “tachyhydrite”. The geological structure observed in the cross section of each borehole showed facies of potash and rock salt in the area. The carnallite and tachyhydrite were deposited in the local salt basin, whereas the rock salt had formed as a ridge, dome or pillow of the salt layer. The sylvite mineral (the best potash mineral for agricultural fertilizer) was deposited between these two structures or at the frank of the dome or pillow. This information supports the salt dome theory that explains the origin of sylvite deposited in Thailand.